Increasing organ donation by presumed consent and allocation priority: Chile - Alejandra Zúñiga-Fajuri (The World Health Organization, 2015)
Chile, a middle-income country, recently joined Israel and Singapore as the world's only countries to require reciprocity as a precondition for organ transplantation. The Chilean reform includes opt-out provisions designed to foster donation and priority for organ transplantation for registered people. Although the reform has had serious difficulties in achieving its mission, it can be reviewed by other countries that seek to address the serious shortage of organs. As increased organ donation can substantially enhance or save more lives, the effect on organ availability due to incentives arising from rules of preference should not be underestimated.